ANALISIS KOMPONEN KIMIA DARI KAYU KURANG DIKENAL DARI KALIMANTAN TIMUR - Gustan Pari; Dadang Setiawan; Saepuloh Saepuloh (Pusat Penelitian dan Pengembangan Hasil Hutan, 2001)
This paper reported the results of chemical components of several lesser known wood species from East Kalimantan. The wood species were Kayu Arang (Diospyros macrophylla), Nyaling (Mastixia trichotama), Penjalin (Drypetes), Lansat Hutan (Lansium) and Kayu Goding (Koilodepes).The analysis were comprised of the determination of holocellulose, hemicellulose, -cellulose, lignin, pentosane; ash content and silicate content. The solubilities in alcohol benzene, cold water, hot water and solubility in NaOH 1 % were also covered. These analyses pertaining to the basic wood characteristics were conducted to assess the ultimate utilization of the wood species as such, especially for pulp manufacture. The result showed that holocellulose content ranged from 71.17-81.20 %, hemicelluloce from 27.51-35.88 %, -celluloce from 43.15-48.73 %, lignin from 22.73-33.60 %. Pentosan from 15.28-18. 79 % ash content from 0.5 -1.34 %, and the silicate content from 0.12-0.49 %. Furhter, the solubilities in cold water ranged from I. 79- 3.24 %, hot water from 5.50- 7.21 %, alcohol benzene from 1.62- 3.65 % and solubility in NaOH I% from 14.21-16.90 %.Based on results of chemical analysis. especially with respect to holocellulose, lignin and pentosan content. most wood species are suitable as raw material for pulp and paper industry. For lansat hutan (Lansium sp), kayu arang (Diospiros macrophylla) and gading (Koilodepes) species, their considerable extractive content as shown by high solubilities in the organic solvent should be considered since it could reveal high wax content as well.